2022
DOI: 10.21037/qims-21-341
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning–based diagnostic evaluation of shear-wave elastography in BI-RADS category 4 breast cancer screening: a multicenter, retrospective study

Abstract: Background: Ultrasound is commonly used in breast cancer screening but lacks quantification ability and diagnostic power due to its low specificity, which can lead to overdiagnosis and unnecessary biopsies. This study evaluated the diagnostic efficacy and clinical utility of adding shear-wave elastography (SWE) to the screening of the Breast Imaging Reporting and Data System (BI-RADS) category 4 breast cancer.Methods: A machine learning-based diagnostic model was constructed using data retrospectively collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Recent research reported that the maximum area of stiffness in malignant tumors was consistently found in the peritumoral stroma rather than inside the tumor (29,30). Potential causes of the "stiff rim" sign have been suggested to be a desmoplastic response and infiltration of tumor cells into the peritumoral stroma (2,31). As a consequence, the tissues surrounding the tumor's edge or periphery are often stiffer (referred to as the "stiff rim") (32), increasing their stiffness by a factor of 2-10 or more (33).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research reported that the maximum area of stiffness in malignant tumors was consistently found in the peritumoral stroma rather than inside the tumor (29,30). Potential causes of the "stiff rim" sign have been suggested to be a desmoplastic response and infiltration of tumor cells into the peritumoral stroma (2,31). As a consequence, the tissues surrounding the tumor's edge or periphery are often stiffer (referred to as the "stiff rim") (32), increasing their stiffness by a factor of 2-10 or more (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, various studies have discussed the diagnostic performance of additional SWE findings for differentiating malignant and benign breast lesions and for evaluating fibroepithelial lesions, including fibroadenomas. 2 , 23 , 27 , 28 , 29 , 30 , 31 Two studies have evaluated the contribution of SWE findings to the diagnosis of fibroadenomas. 2 , 29 Evans et al 2 evaluated both B-mode US and SWE features for diagnosing fibroadenomas in the absence of biopsy, concluding that, because clinically benign solid breast lesions with benign B-mode US and SWE findings exhibited no malignant transformation, biopsy and follow-up procedures were unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of SWE in the diagnosis, differentiation, efficacy evaluation and prediction of breast cancer was obvious ( 13 , 14 , 27 ). One study demonstrated the superior predictive value of Emax in combination with BI-RADS category 4a in breast cancer screening ( 28 ). Another research found that Emax was the best parameter for classifying breast lesions, with a maximum AUC of 0.90 (95%CI: 0.77-1.00) ( 29 ).…”
Section: Discussionmentioning
confidence: 99%